Determinants of Going Concern Audit Opinions in Financially Distressed Manufacturing Firms - Muhammad Mas Said; Syaiful Hifni; Atma Hayar (Universitas Darwan Ali, 2025)
This study aims to examine the effect of public accounting firm (PAF) size, audit tenure, auditor switching, and the disclosure of management plans on going concern audit opinions in manufacturing companies experiencing financial distress. The increasing number of financially distressed firms and corporate delistings on the Indonesia Stock Exchange in 2017 highlights the crucial role of auditors in providing early warning signals regarding uncertainties in business continuity. The data were obtained from the financial statements of manufacturing companies for the 2016–2018 period and were selected using a purposive sampling technique, resulting in a sample of 45 companies with a total of 135 observations. Logistic regression was employed as the analytical method. The results indicate that PAF size, audit tenure, and auditor switching do not have a significant effect on going concern audit opinions, suggesting that auditors maintain their independence and professionalism. In contrast, the disclosure of management plans has a positive and significant effect on going concern audit opinions, indicating that auditors perceive such disclosures as signals of an increased risk of a company’s inability to sustain its business continuity. These findings provide important implications for auditors, management, and regulators in enhancing audit quality and financial reporting transparency in Indonesia.